International Information System for Agricultural Sciences and Technology and Indian Participation - Raj, Hans; Kaushik, V.S. (DESIDOC Journal of Library & Information Technology, 2011)
The paper briefly describes the history and development of agricultural research information system(AGRIS), its network, documentation tools, products/services, HRD and capacity building programme. Anattempt has been made to showcase the contribution of India in AGRIS development. Limitations and problemsfaced during AGRIS input preparation have been discussed in detail and an action plan is suggested for furtherprogress and success of AGRIS programme in India. doi: 10.14429/djlit.32.2.1401